The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11999-012-2761-1
|View full text |Cite
|
Sign up to set email alerts
|

Can Joint Contact Dynamics Be Restored by Anterior Cruciate Ligament Reconstruction?

Abstract: Background Rotational kinematics has become an important consideration after ACL reconstruction because of its possible influence on knee degeneration. However, it remains unknown whether ACL reconstruction can restore both rotational kinematics and normal joint contact patterns, especially during functional activities. Questions/purposes We asked whether knee kinematics (tibial anterior translation and axial rotation) and joint contact mechanics (tibiofemoral sliding distance) would be restored by double-bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 39 publications
1
54
1
1
Order By: Relevance
“…[98] Dual fluoroscopy and dynamic stereo-radiography is becoming more widely accessible because it provides better precision and more reliability than the use of high-speed cameras or marker based motion capture systems. [98] Hoshino and colleagues[99] investigated whether knee kinematics and joint contact mechanics can be restored after ACLR with a double-bundle or single-bundle graft using dynamic stereo x-ray to capture biplane radiographic images. The athletes were on average a little more than one year out from ACLR and were performing downhill treadmill running.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%
See 1 more Smart Citation
“…[98] Dual fluoroscopy and dynamic stereo-radiography is becoming more widely accessible because it provides better precision and more reliability than the use of high-speed cameras or marker based motion capture systems. [98] Hoshino and colleagues[99] investigated whether knee kinematics and joint contact mechanics can be restored after ACLR with a double-bundle or single-bundle graft using dynamic stereo x-ray to capture biplane radiographic images. The athletes were on average a little more than one year out from ACLR and were performing downhill treadmill running.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%
“…The athletes were on average a little more than one year out from ACLR and were performing downhill treadmill running. [99] The study concluded that neither ACLR procedure restored normal knee kinematics or medial joint sliding. [99] In addition, developments in quantitative magnetic resonance imaging (MRI) have allowed researchers to evaluate the composition and structures within the knee.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%
“…Women are at increased risk (up to 10-fold) for ACL injury in comparison to men when playing the same sport [29]. Despite reasonable success of ACL reconstruction, the current gold standard of treatment, in restoring the gross stability of the ACL-deficient knee, it fails to restore normal joint kinematics and kinetics [8,22,24,25,43,52]. Moreover, ACL reconstruction is associated with reduced activity level [5], an increased rate of secondary injury [48], and high risk of posttraumatic osteoarthritis (OA), up to 74%, even with advanced anatomic reconstruction techniques [13,32,33,40,50,56].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the mechanical environment of the knee after an ACL injury and reconstruction is not well understood. While altered knee contact kinematics are known to exist after ACL injuries 3,8,16,28 and can persist after reconstruction, 1,10,23 joint contact forces in the ACL-injured knee are less well described. Joint contact force is the magnitude of load that is applied perpendicular to the articular surface and represents the compressive loading of the joint as a whole.…”
mentioning
confidence: 99%